Applicability Analysis of Peanut Addition to Button Mushroom Substrate Supplement Formulation - Caitano, Cinthia Elen Cardoso [UNESP]; Vieira Júnior, Wagner Gonçalves [UNESP]; Alves, Lucas da Silva [UNESP]; Teixeira, Pedro Afonso Gomes [UNESP]; de Paula, Laura Cristina [UNESP]; Zied, Diego Cunha [UNESP] (MDPI, 2024)
This study evaluated the agronomic response of Agaricus bisporus strains supplemented with various formulations containing soybean meal and peanut grain residue, which has traces of aflatoxins. Six supplement formulations were developed, starting with 100% soybean meal and no peanuts and gradually increasing peanut inclusion by 10% while proportionally reducing soybean meal until reaching a 50% soybean and 50% peanut ratio. The substrate was produced using the traditional method and supplemented at two points: during inoculation and when adding the cover layer. The strains ABI 22/01 and ABI 22/02 were utilized. After the supplementation and incubation periods in a controlled environment (19 ± 2 °C and 85 ± 5% humidity), the fungus was cultivated. Three production cycles were conducted, evaluating yield, weight, number of mushrooms, biological efficiency, and precocity. The concentrations of aflatoxins in the supplements and mushrooms were determined, along with the nutritional characterization of the substrate and supplements. The inclusion of up to 30% peanuts in the supplement formulation was beneficial for yield, particularly for ABI 22/01. The formulation with 80% soybean meal and 20% peanuts resulted in a 53% yield increase compared to the control. Traces of aflatoxin were found in the supplement but not in the mushrooms.
Keywords: aflatoxins; Agaricus bisporus; strains; supplementation; yield